2018
DOI: 10.1016/j.pscychresns.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Increases in orbitofrontal cortex thickness following antidepressant treatment are associated with changes in resting state autonomic function in adolescents with major depression – Preliminary findings from a pilot study

Abstract: In adults with major depressive disorder (MDD), effective treatment has been associated with increases in both heart rate variability (HRV) and cortical thickness. However, the impact of treatment on these indices has not yet been examined in adolescents. Cortical thickness and HRV were measured in twelve adolescents with MDD before and after 8 weeks of treatment with a selective serotonin reuptake inhibitor (SSRI). We examined treatment-related changes in depression symptoms, HRV, heart rate (HR), and cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 56 publications
1
12
1
Order By: Relevance
“…Here's the good news: these phenomena are reversible! In line with research in adults (Chambers & Allen, 2002; Jang, Hwang, Padhye, & Meininger, 2017), we have previously shown, that HRV re‐increases following antidepressant treatment with selective serotonin reuptake inhibitors in adolescents with depression (Koenig et al, 2018). Clinical improvement (decrease in depression severity) was associated with increased HRV and decreased HR.…”
Section: A Dynamical Model Of Neurovisceral Integrationsupporting
confidence: 88%
“…Here's the good news: these phenomena are reversible! In line with research in adults (Chambers & Allen, 2002; Jang, Hwang, Padhye, & Meininger, 2017), we have previously shown, that HRV re‐increases following antidepressant treatment with selective serotonin reuptake inhibitors in adolescents with depression (Koenig et al, 2018). Clinical improvement (decrease in depression severity) was associated with increased HRV and decreased HR.…”
Section: A Dynamical Model Of Neurovisceral Integrationsupporting
confidence: 88%
“…Multi-modal assessments of autonomic nervous system function showed that acute tVNS was associated with an increase in HRV and a decrease of HR only in controls. The absence of effects in patients with MDD suggests that ANS regulation is not susceptible to acute-tVNS, but may require prolonged therapeutic intervention to show meaningful effects (Koenig et al, 2018 ). In line with the findings of prior meta-analyses (Kemp et al, 2010 ; Koenig, Kemp, Beauchaine, Thayer, & Kaess, 2016 ), patients with MDD from the present sample showed greater HR and lower HRV compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous cortical thickness study using the same dataset, the increased thickness of the left medial orbitofrontal cortex and the correlations between clinical improvement and increased cortical thickness of the left lateral orbitofrontal cortex and superior frontal cortex were found [ 107 ], which potentially relate to increased connectivity. The bilateral middle temporal gyrus also shows a decreased clustering coefficient and local efficiency but not the nodal centrality.…”
Section: Discussionmentioning
confidence: 95%